How hot is too hot? Live‐trapped gray wolf rectal temperatures and 1‐year survival - Shannon M. Barber‐Meyer; L. David Mech (Wildlife Society Bulletin)
ABSTRACT The ability of physically restrained and anesthetized wolves to thermoregulate is lessened and could lead to reduced survival, yet no information is available about this subject. Therefore, we analyzed rectal temperatures related to survival 1 year post‐capture from 173 adult (non‐pup) gray wolves (Canis lupus) captured in modified foot‐hold traps for radiocollaring during June–August, 1988–2011, in the Superior National Forest of northeastern Minnesota, USA. The maximum observed rectal temperature (“maxtemp,” ° F, ° C) in each wolf during capture (x¯ = 104.0, 40.0; SD = 2.0, 1.1; min. = 95.9, 35.5; max. = 108, 42.2) was not a significant predictor of survival to 1 year post‐capture. Although no weather or morphometric variable was a significant predictor of maxtemps, wolves initially anesthetized with ketamine–xylazine rather than telazol®–xylazine averaged higher maxtemps. This information does not fully address possible effects of high body temperatures related to live‐capture and handling of wolves, but it does provide a useful waypoint for future assessments of this relationship and a reassurance to wildlife practitioners that the maxtemps observed in our study did not appear to affect 1‐year survival. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.